Preparation and Characterization Of (ZnO-TiO2) nanoparticles and studying their effect of Photo degradation Ampicillin - Al Jurdh, Maisam (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2024)
In this research, the photodegradation of the ampicillin antibiotic (AMP) in an aqueous solution was studied by using ZnO–TiO2 nanoparticles prepared via the wet incipient impregnation method with TiO2 and Zn(NO3)2⋅6H2O as precursor materials using three different ratios of both oxides (1:1, 0.5:1, 1:0.5). The effects of different molar ratios of the prepared nanoparticles and ultraviolet radiation from sun rays and a UV lamp were studied. We utilized SEM, XRD, and EDX characterization techniques to study the structural features and morphology of the nanoprepared oxide. The removal of the antibiotic ampicillin was studied using an ultraviolet device at a wavelength of 254 nm in the presence of oxide nanoparticles and two radiation sources. The removal rate was 98% when using a composite oxide (ZnO-TiO2) in a proportion of 0.5:1 and applying solar radiation.